INVESTIGATING THE CONNECTION BETWEEN SOIL RESPIRATION AND OAK FOREST DENSITY CLASSES - Antrix, Antrix; Parul, Parul M. K. (International Journal of Allied Sciences (IJAS), 2023)
Soil is a vital trace element in terrestrial ecosystems, and understanding its fertility status is essential for plant growth. This study investigates the nutrient status of soil and its relationship with different density classes of Oak forests in Uttarakhand, India. The sites were selected from Dehra Dun, Pauri Garhwal, and Tehri Garhwal districts, with varying altitude, latitude, and longitude. Soil samples were collected up to a depth of 0-30 cm in each area, with seasonal sampling conducted. Results revealed that soil pH was mildly acidic in dense oak forests, followed by moderate and open forests. An increase in soil nutrients was observed with the increasing density of Oak forests, and nutrient availability was higher in dense forests compared to moderate and open oak forests. This trend was consistent across all selected oak forest density classes. A correlation was found between soil physicochemical and biological properties under different density classes and seasons (winter, summer, monsoon). The pH value and bulk density were negatively correlated with soil organic carbon, available nitrogen, phosphorus, exchangeable potassium, bacterial colony, microbial biomass carbon, and soil respiration. The soil pH was acidic in the upper horizon, and its acidity increased with decreasing density classes. The study also found that high humus content was present in dense forest soils, with microbial biomass carbon negatively correlated with phosphorus during winter and summer seasons. In the monsoon season, soil pH was significantly negatively correlated with soil organic carbon, available nitrogen, phosphorus, exchangeable potassium, bacterial colony, microbial biomass carbon, and soil respiration. Furthermore, these soil properties were positively correlated with each other. The analysis showed that higher tree density in oak forests resulted in increased nutrient values, with dense forests producing more nutrients than moderate and open forests. A positive correlation was found between the density classes (dense>moderate>open oak forest), while a negative correlation was observed with soil pH and bulk density, which increased with decreasing density classes.